2008
DOI: 10.1002/dvdy.21623
|View full text |Cite
|
Sign up to set email alerts
|

Gene nomenclature guidelines for the planarian Schmidtea mediterranea

Abstract: We describe a gene nomenclature system for the freshwater planarian Schmidtea mediterranea. Guidelines are specified for designating names for genes and proteins, as well as for describing RNA-mediated genetic interference (RNAi) experiments. The proposed conventions aim to avoid multiple names being ascribed to single genes and to establish a uniform, simple method for naming genes in S. mediterranea that is readily understood by researchers working on planarians and other organisms. Developmental Dynamics 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Sequences were excluded if they shared similarity with genes previously annotated to be other than neuropeptide prohormones. All genes were named according to the S. mediterranea genome nomenclature guidelines [105].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were excluded if they shared similarity with genes previously annotated to be other than neuropeptide prohormones. All genes were named according to the S. mediterranea genome nomenclature guidelines [105].…”
Section: Methodsmentioning
confidence: 99%
“…A previous phylogenetic study identified this gene as one of two planarian Zic family members (previously designated as zicA and zicB ), with representatives in all animals [45]. We renamed the zicA gene Smed-zic-1 (hereafter referred to as zic-1 ) in keeping with the Schmidtea mediterranea gene nomenclature guidelines [53].…”
Section: Resultsmentioning
confidence: 99%
“…An additional Zic-family gene in the S. mediterranea genome, formerly referred to as zicB , we renamed Smed-zic-2 (here after referred to as zic-2 ) in keeping with the S. mediterranea guidelines for gene names [53]. z ic-2 was expressed in the anterior of uninjured animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Planarians were starved for at least 1 week prior to experiments. Genes and RNAi experiments were named using the nomenclature proposed by Reddien et al (2008).…”
Section: Animalsmentioning
confidence: 99%